PARTISIPASI MASYARAKAT DALAM PEMELIHARAAN KESEHATAN LINGKUNGAN PERMUKIMAN DI KECAMATAN PAUH DUO KABUPATEN SOLOK SELATAN - azmi julia indra; afdhal afdhal (JURNAL BUANA, 2019)
This study aims to determine community participation in the maintenance of residential environmental health in Pauh Duo Subdistrict, seen from the management of house hygiene, clean water management and waste and household waste management. This type of research is quantitative descriptive. The study population was all family heads who were or residing in the Pauh Duo sub-district of South Solok Regency which numbered 4,985 heads of families. The research sample was taken by the method of "Propotional Random Sampling" using the Slovin formula so that a sample of 100 families was obtained. Data analysis is percentage analysis. The results of the study show that: (1) Management of cleanliness of houses in Pauh Duo sub-district is seen from attention, responsibility and generally high actions, (2) Management is clean water viewed from attention, responsibility and community actions grouped into categories high and (3) Community participation in waste management and household waste is seen from attention, responsibility and actions including the high category